Identification of a mechanism for mechanical deseeding of tamarind - ANAGHA BALAN ARATHY KRISHNAN JOSNA K LIBINA STEPHEN; Er. Shivaji K. P (Guide) (Tavanur 2016 DEPARTMENT OF FARM POWER MACHINERY AND ENERGY)
Identification of a mechanism for mechanical deseeding of tamarind
Identification of a mechanism for mechanical deseeding of tamarind